Effects of the Reading Practice Platform (Readvise) in Developing Self-Regulated Reading Skills of Tertiary Students in L2 Learning - Anait Akopyan; Katrin Saks (MDPI AG, 2022)
Reading, as one of the four basic language skills, activates language learning. Tertiary-level students often undermine this opportunity and rarely read anything in addition to their course assignments. Rapid technological developments offer additional possibilities in this domain. The present study aims to define to what extent the specifically designed web-based reading platform (Readvise) can support and improve students' second language reading skills with the intent to transform them into self-regulated reading (SRR) skills. The focus of this design-based research is 39 undergraduate students who study English as a second language (L2). According to the results, through the elimination of the main barriers and uncertainties declared by the students when reading independently in L2, the platform contributes to the advancement of L2 reading skills of the students, encourages changes in their L2 reading behaviour, fosters metacognitive abilities, and reinforces intrinsic reading motivation. When supported consistently through the platform, these features can ensure the development and enhancement of SRR skills in the long run, contributing equally to the improvement of the students' L2 proficiency level.